‘We Say Sorry’: Apology, the Law and Theatricality - Theron Schmidt (Law Text Culture, 2010)
When ideas about theatre are used to describe political events, the theatrical is usually made to stand for that which is undesirable, inauthentic and empty about political life: we might describe a particular speech or gesture as ‘only theatre’, or use language such as ‘playing politics’ or ‘political drama’ to denounce the way self-referential questions about character or personal intrigue have obscured the ‘real’ issues of politics. In contrast to this dismissive usage, I would like to explore the ways that theatricality’s apparent failures or shortcomings might be themselves generative of political potential. My approach here is to consider certain problems of speech and gesture in the political realm as essentially theatrical problems — problems for theatre, but also ideas that theatricality makes problems of — such as problems of representation, authenticity and spectatorship. I will explore the theatricality at work in three examples of publicly performed discourse: Kevin Rudd’s official apology in 2008 to the Indigenous peoples of Australia; a gallery artwork by Carey Young which, in its entirety, is a legal disclaimer of its status as art; and a text and video work by Lebanese-born artist, Rabih Mroué, in which the artist offers an apology for the Lebanese civil war.